Health Risk of Cadmium and Lead in the Rice Cultivated in Meydavood, Khoozestan Province, Iran - marzieh kolahkaj; sedigheh battalebloie (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: High accumulation of heavy metals in food chain at critical doze has detrimental effects on the living organisms. Regarding the fact that rice is highly consumed as a main dish in Iran, this study aimed to investigate the level of cadmium and lead in Meydavood rice, as well as their effects on the inhabitants of this region. Methods: This study was conducted on 10 rice samples from Meydavood farmlands, located in Khoozestan Province, Iran. After preparation, samples were analyzed for lead and cadmium using inductively coupled plasma mass spectrometry. The levels of lead and cadmium doses in daily rice consumption for each person (110 grams for 70 kg body weight) were calculated using SPSS statistical software. Results: The mean concentrations of cadmium and lead in rice samples were 0.02 and 1.07 mg/kg, respectively. Based on the obtained results, the level of cadmium was lower and the level of lead was higher than the standard level proposed by the World Health Organization (WHO). The total weekly intake of cadmium and lead through rice consumption was evaluated based on provisional tolerable daily intake determined by WHO/Food and Agriculture Organization (FAO). Conclusion: According to provisional tolerable daily intake, it can be concluded that the daily intake of cadmium and lead through rice was in the standard range recommended by WHO and FAO. In addition, it is important to have a healthy diet to protect the health of the inhabitants due to the high levels of cadmium and lead in rice samples, and other agricultural products.